(untitled) (Tzintzun, Revista de Estudios Históricos, 2019)
This article is about the transition of female surveillance from a private to a public space. Using administrative documentation, it examines some of the characteristics of three groups of women, scarcely acknowledged in history: the female prision guards, the prostitute keepers, and the first police women. It also analyses how they came to find a place in a traditionally masculine space, and it supports the idea that despite the authority and presence they gained, they continued performing activities considered â€œfeminineâ€.